Larval survival strategy during winter of Chordodes nobilii Camerano, 1901 (Gordiida, Nematomorpha) - Zanca, Fernanda Mariel (2007)
There are numerous open questions concerning the life cycle of Gordiida (Nematomorpha), especially about egg development and viability of larvae during winter, when the temperature of freshwater environments where they inhabit is low. On the basis of experimental studies we demonstrate that egg development of Chordodes nobilii takes 20-25 days at 22°C and 45-55 days at 5°C. We also observed that larvae of C. nobilii obtained from egg strings at 5°C and maintained at that temperature during six months remained inside their egg shells as a survival strategy.